Analysis on the Spanish, English and European law on the extension to the injured third party of the arbitration agreement and the applicable law of maritime civil liability insurance - Sierra Noguero, Eliseo (CUADERNOS DE DERECHO TRANSNACIONAL, 2023)
The content is the analysis of the main British; Spanish and European court cases that have had to resolve whether the usual clauses of applicable law and arbitration agreement of whether protection and indemnity insurance are enforceable or not against the injured third party by the actions of the insured shipowner. In British Law; it is considered opposable; as in Spanish Law since the “Seabank” judgment of 2003. However; the Court of Justice of the European Union in the “Prestige” case of 2022 considers that the arbitration agreement cannot be opposable to the injured third party who exercises direct action against the maritime civil liability insurer.